Efeito de agroquímicos sobre a microbiota intestinal de abelhas - Soares, Kilmer Oliveira (2023)
Although bees are responsible for ensuring the ecological stability of numerous environments, they are susceptible to various human activities that can result in the extinction of species due to environmental degradation, such as the use of agrochemicals. Africanized bees (Apis mellifera scutellata x spp.) play a significant role in the commercialization of beekeeping products in Brazil. However, very little is known about these bees, since they originated recently in Brazil (1956), through accidental crossing involving some European (Apis mellifera spp.) and African (Apis mellifera scutellata) bees. Considering the fundamental role of the intestinal microbiota of bees for health and, consequently, pollination of the various biomes, this thesis aims to investigate the composition of the intestinal microbiota of Africanized bees in relation to European and African bees, in addition to evaluating, experimentally, changes in the microbiota associated with exposure to agrochemicals. Chapter 1 (The honey bee gut microbiome: a review from the perspective of bees threatened by agrochemicals) deals with a review of the intestinal microbiome of bees and its changes associated with the use of agrochemicals. In Chapter 2 (Africanized honey bees (Apis mellifera scutellata x spp.) gut microbiota: is it similar to African or European bees?), we present a comparative evaluation in silico, using 16S rRNA gene sequencing data from 126 bee intestinal samples European (n=34), African (n=82) and Africanized (n=10). The results demonstrated that the intestinal microbiota of Africanized bees is more similar to that of European bees, although the relative abundance of the genus Snodgrassella was higher in Africanized and African bees compared to European bees. The genus Gilliamella was more abundant in Africanized bees compared to African bees. Chapter 3 (Tetracycline exposure alters key gut microbiota in africanized honey bees (Apis mellifera scutellata x spp.) aimed to experimentally evaluate the effect of exposure to the antibiotic tetracycline in Africanized bees. (CON: fed daily with syrup (10 g) composed of a 1:1 solution of demerara sugar and water, plus a solid protein diet (10 g) composed of 60% soy extract and 40% sugar syrup) and exposed group (TET: fed identically to CON, but with the addition of tetracycline hydrochloride at a dose of 450 μg/g to sugar syrup) were obtained from each group before (day 0) and after exposure to tetracycline (days 3, 6 and 9) After sequencing the V3-V4 region of the 16S rRNA gene in Illumina MiSeq, and processing through QIIME2 and DADA2, the results showed significant differences in the composition (Jaccard) and diversity (Shannon) of the microbiota intestinal, sen such differences become more accentuated as the exposure time increases. TET reduced the relative abundance of Bombella and Fructobacillus, along with a decrease in essential microbiota such as Snodgrassella, Gilliamella, Rhizobiaceae and Apibacter. As these microorganisms are critical for nutrient metabolism and pathogen defense, it is possible that their decrease could negatively affect bee health. Chapter 3 (The effects of zinc and laboratory emerge date on honey bee gut microbiota) refers to an experimental study on the effect of zinc on the microbiota of European bees. Zinc is often found in agricultural runoff as it is used in fertilizers, insecticides and food additives. Studies on the supposed effects of zinc on bee health are, however, scarce. In this study, bees were exposed to seven concentrations of zinc (0, 50, 100, 250, 500 or 1000 mg/L). Survival was only minimally impacted (>89% survival) at zinc concentrations up to 100 mg/L. To evaluate the effects of zinc on the intestinal microbiota, the bees were exposed to concentrations of 5 or 100 mg/L of zinc. Gut samples were collected before (day 0) and after exposure (days 3, 6 and 9). Abdominal contents were subjected to DNA extraction and sequencing of the V3- V4 region of the 16S rRNA gene (V3-V4) on an Illumina MiSeq. Sequences were filtered and processed through QIIME2 and DADA2. Although exposure to zinc has minimal effects on bacterial DNA concentrations and absolute microorganism counts, a significant difference in concentrations was observed between the different days of emergence (moment that the bee emerges from the brood comb). In this situation, a decrease in bacterial concentrations was observed. Significant differences in taxonomic diversity and abundance were observed in bees exposed to the highest concentration of zinc (100 mg/L), in which a reduction of several beneficial taxa (Lactobacillus, Rhizobiaceae, Gilliamella) and an increase of Paenibacillus, a taxon potentially pathogenic. The results indicated that the exposure to zinc, even at relatively low levels, can negatively compromise bee health, even if survival is not drastically affected.